Hak dan Kewajiban Terkait Perkawinan Angkap Bagi Masyarakat Gayo di Tinjau dari Hukum Islam - Azra Zahrani (SAMAWA, 2024)
Marriage is considered valid if it complies with both formal and informal requirements, including provisions in Law Number 1 of 1974 concerning Marriage, Presidential Instruction Number 1 of 1999 concerning the Compilation of Islamic Law, and religious teachings. Despite being acknowledged by both the legal and religious frameworks, the evolving times have brought changes, leading to the emergence of traditional marriage forms such as Angkap marriage in indigenous communities. Often conducted without legal and fiqh law procedures, Angkap marriage is a distinct traditional practice among the Gayo people. This research aims to comprehend marriage practices in Gayo society, specifically focusing on Angkap marriage, and analyze the relationship between these practices and religious and cultural norms. Utilizing qualitative research methods and a legal history approach, the findings reveal that Angkap marriage in Gayo society has undergone changes over time. Husbands in Angkap marriages forfeit their inheritance rights, yet their responsibilities for financial support persist. These changes align with economic and educational dynamics, indicating that new couples tend to be more financially independent and possess financial autonomy. While Angkap marriage reflects an adaptation to social and economic conditions, its impact on individual rights and obligations, especially concerning inheritance and the husband's role in the family, remains a focal point in discussions about traditional Gayo marriages.